The Effect of Salak (Salacca zalacca) Leaf Silage in Complete Feed on Digestibility and Characteristics in Vitro Fermantation - Nasution, Riska Romaito; Trisna, Ade; Ginting, Simon P (ANIMAL PRODUCTION, 2023)
The purpose of this study is to establish the best proportion of salakleaf silage utilisation in complete feed based on dry matter digestibility, organic matter digestibility, pH value, VFA generation, and NH3 concentration. The method used in this study was experimental with a 4 x 4 Randomized Block Design (RBD), using four distinct treatment ratios and 4 times rumen fluid collection as a repeat group. The percentage of salakleaf treatments in complete feed were: P0 (15% elephant grass in complete feed), P1 (15% salakleaf in complete feed), P2 (30% salakleaves in complete feed) and P3 (45% salak leaves in complete feed). The observed variables consisted of dry matter digestibility, organic matter digestibility, pH value, VFA production, and NH3 concentration. The mathematical model used is an analysis of variance and if there are differences between treatments it is continued with the DMRT (Duncan's Multiple Range Test) test (Steel and Torrie, 1991). The results revealed that the treatment ration had no significant (P>0.05) influence on pH value and had a very significant effect (P<0.01) on dry matter digestibility, organic matter digestibility, VFA production, and NH3 concentration. This study concluded that using 30% silage of salakleaves in complete feed could maintain the pH value and increase the dry matter digestibility, organic matter digestibility, pH value, VFA production, and NH3 concentration.